2003
DOI: 10.1161/01.cir.0000044940.65226.1f
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Infections and Subsequent Cardiovascular Events in the Heart Outcomes Prevention Evaluation (HOPE) Study

Abstract: Background-Limited prospective epidemiological data are available on the relation between exposure to Chlamydia pneumoniae, Helicobacter pylori, cytomegalovirus (CMV), and hepatitis A virus (HAV), individually or as a total pathogen score, and human cardiovascular (CV) disease. Methods and Results-We analyzed enrollment sera from 3168 Canadian patients in the Heart Outcomes Prevention Evaluation (HOPE) study for antibodies to C pneumoniae, H pylori, CMV, and HAV and measured the relation between serostatus and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
94
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(101 citation statements)
references
References 31 publications
7
94
0
Order By: Relevance
“…For example, a prospective nested case-control study found that H. pylori-IgG positivity is not associated with the risk of myocardial infarction or stroke in middle-aged Japanese individuals 45) . Additionally, neither CagA-negative nor CagApositive H. pylori infection has been shown to be associated with an increased risk of myocardial infarction and stroke in Germany 44) , consistent with the results obtained from other countries, including England 47) , Greece 46) , Canada 48) and China 49) . The discrepancies reported concerning the association between H. pylori HP: Helicobacter pylori, CIMT: carotid intima-media thickness, AMI: acute myocardial infarction, CHD: coronary heart disease, IHD: ischemic heart disease, IS: ischemic stroke, UBT: urea breath test.…”
Section: Potential Mechanisms Through Which H Pylori May Contribute supporting
confidence: 88%
“…For example, a prospective nested case-control study found that H. pylori-IgG positivity is not associated with the risk of myocardial infarction or stroke in middle-aged Japanese individuals 45) . Additionally, neither CagA-negative nor CagApositive H. pylori infection has been shown to be associated with an increased risk of myocardial infarction and stroke in Germany 44) , consistent with the results obtained from other countries, including England 47) , Greece 46) , Canada 48) and China 49) . The discrepancies reported concerning the association between H. pylori HP: Helicobacter pylori, CIMT: carotid intima-media thickness, AMI: acute myocardial infarction, CHD: coronary heart disease, IHD: ischemic heart disease, IS: ischemic stroke, UBT: urea breath test.…”
Section: Potential Mechanisms Through Which H Pylori May Contribute supporting
confidence: 88%
“…However, CMV did predict secondary risk (death/myocardial infarction) in patients with pre-existing coronary artery disease especially in those with elevated C-reactive protein or interleukin-6 (IL-6) (27,28). Similar results were obtained in the HOPE (Heart Outcomes and Prevention Evaluation) study showing that out of the four pathogens tested (Cpn, Hpyl, hepatitis A, CMV) only CMV serostatus was predictive of cardiovascular events (29). The association with CMV seems to be more pronounced in connection with rapidly progressing atherosclerotic processes such as coronary restenosis after angioplasty or vascular surgery (18), and this observation might be of relevance to CAV in view of its rapid time course.…”
Section: Seroepidemiological Studiessupporting
confidence: 53%
“…Adjusted risk for the seropair with the highest risk for posttransplantation CMV disease (donor-positive/recipientnegative) approached but did not reach our chosen level of statistical significance (P ϭ 0.03). In accordance with these unadjusted risk estimates, CMV infection has been linked with atherosclerotic risk among heart transplant recipients (35) and general patients without transplants (36). As approximately 15% of serologic pairing information was missing, failure to detect an independent association of CMV seropairing with PTMI may reflect misclassification error, which tends to reduce the estimated statistical significance of effects.…”
Section: Predictors Of Ptmimentioning
confidence: 65%